Composite tissue columella wedge excision for nasal tip overprojection - Röjdmark, Jonas; Fischer, Sebastian (Plastic and reconstructive surgery, 2022)
Background: -The overprojected nasal tip is a challenge in facial surgery. Although several techniques are available, none has been proven to be superior. The aim of this study was to introduce a novel approach to overcome nasal tip overprojection and to evaluate its safety and efficacy. - Methods: -All patients with protruding nasal tip who underwent correction by means of a novel columella wedge technique were included in this study. In addition to detailed description of the novel surgical approach, its efficacy was analyzed by comparison of preoperative and postoperative nose dimensions. In addition, patients were examined during follow-up, and complication and revision rates were determined. - Results: -Forty-two patients were included in this study. Columella wedge technique involved resection of a 2- to 5-mm section of the middle part of the columella. Postoperatively, nose projection and length decreased by 9 and 12 percent, respectively. The relation between projection and length of the nose changed from 0.68 preoperatively to 0.61 postoperatively. This difference was statistically significant (p = 0.002). After a mean follow-up of 28 months (range, 6 to 144 months), revision operations were necessary in seven patients (16.7 percent). No instabilities, impairment of breathing, or other complications occurred. - Conclusion: -The introduced columella wedge technique is efficient and safe for correction of the overprojected nasal tip. - CLINICAL QUESTION/LEVEL OF EVIDENCE: - Therapeutic, IV.